The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1055/s-0042-1749436
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Interleukin-6/Signal Transducers and Activators of Transduction-3/Hypoxia-Inducible Factor-1α Signaling Pathway Suppressed the Growth of Infantile Hemangioma

Abstract: Objective This study aims to evaluate the expression of interleukin 6 (IL-6) in patients with infantile hemangioma (IH) and investigate the role of the IL-6/signal transducers and activators of transduction-3 (STAT3)/hypoxia-inducible factor-1α (HIF-1α) pathways in the progression of IH. Methods Serum samples were obtained from the patients with IH and normal infants to measure IL-6 expression. Hemangioma-derived stem cells (HemSCs) were transfected with small interfering RNA (siRNA) targeting IL-6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…27 Silencing of HIF-1a limits the viability and migration rate of HemECs. 28 Propranolol blocks the proliferation, tube formation, and migration of HA cells via the HIF-1α dependent mechanisms. 29 Thus HIF-1α amplified the more aggressive behaviour of HemECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Silencing of HIF-1a limits the viability and migration rate of HemECs. 28 Propranolol blocks the proliferation, tube formation, and migration of HA cells via the HIF-1α dependent mechanisms. 29 Thus HIF-1α amplified the more aggressive behaviour of HemECs.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, repression of the HIF‐1a‐VEGF axis leads to the antiproliferative property of curcumin in HemECs 27 . Silencing of HIF‐1a limits the viability and migration rate of HemECs 28 . Propranolol blocks the proliferation, tube formation, and migration of HA cells via the HIF‐1α dependent mechanisms 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Many vascular malformations share similar aberrant molecular signaling pathways with cancers and inflammatory disorders ( Pang et al, 2020 ). It is reported that inhibiting the IL-6/STAT3/HIF-1α signaling pathways could suppress IH growth ( Maimaiti et al, 2022 ). These results indicated that the hub genes were involved in several signaling pathways mediated by growth factor and immune gene, which play a critical role in regulating endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 binds to gp160, then activates STAT3/HIF-1α, which promotes the proliferation of Foxp3 + regulatory T (Treg) cells and reduces activity and migration of hemangioma-derived stem cells ( 25 , 26 ). IL-17 induces defective autophagy through interacting with STAT3/HIF-1α and causes inflammatory death of keloid fibroblasts ( 27 ).…”
Section: Hif-1α Signaling Pathwaymentioning
confidence: 99%